"The student drives the car, right?": trans students and narratives of decision-making in schools. Issue 4 (4th July 2018) - Frohard-Dourlent, Hélène
Abstract: With growing awareness of the negative school experiences of trans students, more schools in North America are working to support such students and create more inclusive educational environments. This paper analyses how 60 educators in British Columbia, Canada talked about the involvement of trans students in decision-making processes at their school. It focuses on a prominent narrative, the 'student in charge' narrative, which suggests that educators should follow the lead of the young trans person to best support them. By centering the expertise of trans student, this narrative has the potential to disrupt cisnormativity in schools and traditional understandings of youth as unreliable. However, educators have also to negotiate dominant discourses about undue adult influence, young age, safety and gender fluidity that tend to undermine their initial commitment to young trans people's self-determination. This paper analyses the effects of these contradictions on how educators respond to demands for recognition by trans students, and discusses the limits of student-led change. It concludes by arguing for more systemic changes that do not require the presence of trans bodies and instead offer possibilities for educational spaces in which all students would experience fewer pressures of gender and sexual conformity.